2017
DOI: 10.1093/jjco/hyx065
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric evaluation of a Persian version of the Death Depression Scale-Revised: a cross-cultural adaptation for patients with advanced cancer

Abstract: Findings revealed that the Persian version of the Death Depression Scale-Revised is valid and reliable, and may be used to assess and evaluate death depression in Iranian patients with advanced cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The following scales were also used in this study: the Death Concern Scale (DCS, Dickstein [26], the Collett-Lester Fear of Death Scale (CLFDS, Collett & Lester, Lesterr) [27,28], the Death Anxiety Scale (DAS, Templer [29], the Reasons for Death Fear Scale (RDFS, Abdel-Khalek [30], and the Death Depression Scale (DDS, Templer, Lavoie, Chalgujian, & Thomas-Dobson [31] (see Table 2). Previous studies have reported translation and adapted processes of the Farsi versions and also desirable reliability and validity for all the scales [[32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45]]. In the present study, the Farsi validated forms of the scales were used.…”
Section: Methodsmentioning
confidence: 99%
“…The following scales were also used in this study: the Death Concern Scale (DCS, Dickstein [26], the Collett-Lester Fear of Death Scale (CLFDS, Collett & Lester, Lesterr) [27,28], the Death Anxiety Scale (DAS, Templer [29], the Reasons for Death Fear Scale (RDFS, Abdel-Khalek [30], and the Death Depression Scale (DDS, Templer, Lavoie, Chalgujian, & Thomas-Dobson [31] (see Table 2). Previous studies have reported translation and adapted processes of the Farsi versions and also desirable reliability and validity for all the scales [[32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45]]. In the present study, the Farsi validated forms of the scales were used.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, to assess the content validity quantitatively, we measured content validity ratios (CVR) and content validity index (CVI) via modi ed kappa coe cient (K). To calculate CVR, the questionnaire was administered to 10 persons representing education and psychometrics, psychology and aging were asked them to evaluate how essential each items on a three-point scale as follows: 1=Not essential, 2=Useful but not essential, and 3=Essential (26,27). Then the CVR was evaluated using the following formula: CVR= (ne -[N/2])/(N/2).…”
Section: Content Validitymentioning
confidence: 99%
“…Five points Likert scale was used (quite important = Score 5, to some extent important = Score 4, moderately important = Score 4, slightly important = Score 4, unimportant = Score 1). The item impact score (IIS) of each item was calculated, and a score ≥1.5 was considered appropriate [28][29][30]. Moreover, item clarity and comprehensibility were improved by striving to editing and rewording.…”
Section: Ambs Reliability and Validitymentioning
confidence: 99%